2010
DOI: 10.1002/dac.1127
|View full text |Cite
|
Sign up to set email alerts
|

Optimal redundancy allocation for high availability routers

Abstract: SUMMARYHow to optimally allocate redundant routers for high availability (HA) networks is a crucial task. In this paper, a 5-tuple availability function A (N , M, , , ) is proposed to determine the minimum required number of standby routers to meet the desired availability ( ) of an HA router, where N and M are the numbers of active routers and standby routers, respectively, and , , and are a single router's failure rate, repair rate, and failure detection and recovery rate, respectively. We have derived the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Grover intensively investigated service availability in ring optical networks. To and Neusy and Tsai et al analyzed a number of long‐haul network architectures from an unavailability point of view and have shown that self‐healing rings dual fed systems offer the highest level of survivability by eliminating service impacts caused by link cuts and other optical fiber components. The research studies in find out that partitioning a network into multiple domains increases the overall availability.…”
Section: Related Workmentioning
confidence: 99%
“…Grover intensively investigated service availability in ring optical networks. To and Neusy and Tsai et al analyzed a number of long‐haul network architectures from an unavailability point of view and have shown that self‐healing rings dual fed systems offer the highest level of survivability by eliminating service impacts caused by link cuts and other optical fiber components. The research studies in find out that partitioning a network into multiple domains increases the overall availability.…”
Section: Related Workmentioning
confidence: 99%
“…If a router fails, the routing functionalities should be seamlessly shifted from one router to another without any disruption of the internal network. A significant challenge has also been the allocation of redundant routers-when these routers exist-to achieve high availability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging Internet applications such as voice-over-Internet protocol (VoIP), teleconferences and multi-party games are adversely affected if rerouting of the data packets occurs because of failures caused by optical fibre cuts, maintenance windows, router reboots, and so on [1][2][3]. Present traffic engineering methods, which are used to optimise link weights, need to recalculate a set of optimal link weights if network failures such as link failures occur.…”
Section: Introductionmentioning
confidence: 99%